Innovations in pediatric dosage forms via 3D printing: Chewing lozenges as an example - Ilić, Milica; Petrović, Maša; Đuriš, Jelena; Cvijić, Sandra (Archives of Pharmacy, 2025)
Three-dimensional (3D) printing offers a versatile platform for producing personalized, age-appropriate dosage forms that address the specific therapeutic and administration needs of the pediatric population. Among several oral dosage forms that can be prepared by 3D printing, chewing lozenges offer numerous advantages, especially for the pediatric population. This study illustrates a formulation development and selection of process parameters for 3D-printed chewing lozenges containing propranolol hydrochloride as a model drug, with potential application in the pediatric population. It also highlights the advantages of 3D printing using the semi-solid material extrusion method. Gelatin and sodium alginate were used as carriers for 3D printing. Immersion time in the calcium chloride solution (tim) and lozenges shape were varied, while the following tests were performed: the assessment of organoleptic properties, mass and thickness variations, melting and disintegration time, drug content and dissolution rate. Initially, the key 3D printing parameters for lozenge production were identified, and then the appropriate formulation was selected. Subsequent testing demonstrated that the shape of lozenges, along with variations in tim, influenced the pharmaceutical-technological characteristics. A formulation based on the combination of gelatin and sodium alginate in 1:3 ratio, immersed for 60 seconds in a calcium chloride solution, was found to be suitable for 3D printing of chewable lozenges.
Keywords: 3D printing; chewing lozenges; propranolol hydrochloride; sodium alginate; gelatin